Incidence of vascular and surgical complications in renal transplants between 2013 and 2014 at Santa Casa de Misericórdia de Goiânia - Bezerra, Ana Paula da Silva Azevedo Nora (2015)
Introduction: Although renal transplantation represents a perspective for individuals with terminal chronic kidney disease, as it is correlated to better quality of life, the morbidity and mortality rates, this procedure is not risk free. The rates of vascular complications vary from 1-23% worldwide, and they are important for being associated with high risk of graft loss. Purpose: To assess the incidence of vascular complications in patients submitted to renal transplantation at Santa Casa de Misericórdia de Goiânia from January 2013 to December 2014. Material and Methods: The following variables were analyzed: renal artery stenosis, renal artery thrombosis, renal vein stenosis, renal vein thrombosis, renal artery pseudoaneurysm, arteriovenous fistula, renal artery kinking, graft twist and infarction. Data collected from medical records: transplanted kidney, donor type, recipient age, recipient gender, rehospitalization and time of cold ischemia. Results: The studied population included 32 patients, being 34.38% female and 65.62% male, with mean age of 46 years. Among surgical complications, there were three cases of urinary fistula (9.3%), two cases of collection (6.25%), one case of graft twist (3.12%) and one case of arterial stenosis (3.12 %). All grafts (100%) came from deceased donor, and there was no graft loss in any case (0%). Conclusion: Although the present study observed a low incidence of vascular complications related to renal transplantation, TIF over 24 hours was the only independent risk factor associated with such event.